Nurturing Transformative Capacities - Adriene Jenik (Journal of Awareness-Based Systems Change)
Climate science points to the need for rapid and substantial social change. Such a fundamental social transformation requires new methods, paradigms and practices that address not only structural, technological, and systems change, but attend to the "inner"/subjective dimensions of transformation. In this paper I develop links between models of change in sustainability transformation literature that include "inner" dimensions of change and Climate Focused Socially Engaged Art, a subset of socially engaged art practice that addresses climate disruption. I then introduce a novel social art practice that attends to these inner dimensions: the ECOtarot. Since 2017, I have performed more than 1500 climate future readings with my ECOtarot deck in public settings throughout the United States and internationally. I found that the structure and form of the ECOtarot method catalyzes an intimate exchange where a new climate future story, connected to the seeker’s life, is co-produced. By outlining the methods of the ECOtarot and placing them within inside-out transformation research for sustainability, I add to literature that insists upon “messier” research methods that reflect lived experiences of our world and acknowledge the importance of senses, emotions, belief and imagination in processes of change. By making the links between Sustainability Transformations theory and Climate Focused Socially Engaged Art practice explicit, I encourage further research and investigation into art methods so that they may be leveraged more fully toward sustainability transformations.